Pluchea dioscoridis extract: A novel therapeutic approach for polycystic ovary syndrome targeting ovarian morphology, dopamine pathways, and neurobehavior in relation to its phytocomponents - Rasha Atta; Sahar Galal Gouda; Marwa Hussein Mohamed; Sherif M. Afifi; Mahmoud I. Nassar; Mohamed A. Farag; Abdelsamed I. Elshamy; Mohamed A. Zayed; Thamer Alqurashi; Shimaa Mohammad Yousof (PLoS ONE, 2025)
Background Polycystic ovarian syndrome (PCOS) is a prevalent endocrine condition associated with hormonal and metabolic abnormalities, as well as behavioral modifications. Aim This research assesses the impact of the chemically profiled Pluchea dioscoridis ethanolic extract and metformin in a letrozole-induced polycystic ovary syndrome rat model. Methods Thirty female Sprague Dawley rats were allocated into five groups: Control, P. dioscoridis (100 mg/kg), PCOS (letrozole, 1 mg/kg), PCOS + Metformin (300 mg/kg), and PCOS + P. dioscoridis (100 mg/kg), letrazole was given for 8 weeks followed by metformin or P. dioscoridis for 21 days. Behavioral assessments, hormone analyses, and dopamine quantifications in the brain were performed. Ovarian histology and immunohistochemical analysis were conducted. Results Letrozole-induced PCOS resulted in heightened depression- and anxiety-like behaviors, along with significant hormonal imbalances compared to the control group (P < 0.05%). Both P. dioscoridis and metformin therapies significantly ameliorated these changes, with P. dioscoridis demonstrating better efficacy. P. dioscoridis medication regulated luteinizing hormone (LH), follicle-stimulating hormone (FSH), testosterone, and estrogen levels, concurrently enhancing cerebral dopamine levels. Histological analysis revealed less cystic follicles and a reinstated normal ovarian architecture in rats treated with P. dioscoridis compared to PCOS group (P < 0.05%). Several flavonoids, nitrogenous compounds and hydroxy cinnamic acid esters were detected in P. dioscoridis samples for the first time utilizing UPLC-ESI-MS analysis. Conclusion The P. dioscoridis ethanolic extract exhibited potential medicinal properties that are equivalent to or surpass those of metformin for treating behavioral, hormonal, and ovarian structural abnormalities produced by PCOS. It significantly improved dopamine levels, hormonal balance, and ovarian histology, rendering it a suitable alternative or complementary treatment for PCOS.